Dental developmental stage affects the treatment outcome of maxillary protraction in skeletal Class III children: A systematic review and meta-analysis - Miao Wei; Zhou Dan; Li Chunjie; Chen Lichun; Guan Min; Peng Yiran; Mei Li (Sciendo, 2021)
Background: The aim of this study was to investigate the effect of the stage of dental development on the treatment outcome of maxillary protraction in skeletal Class III children.